Optical features of novel semiconducting crystals Tl1–xGa1–xSnxSe2 (x=0.05; 0.1) - Tsisar, O.V.; Piskach, L.V.; Marushko, L.P.; Kadykalo, E.M.; Myronchuk, G.L.; Makhnovetz, A.; Denysyuk, M.; Reshak, Ali H.; El-Naggar, A.M.; Albassam, A.A.; Kityk, I.V. (Elsevier, 2020)
The results of the novel Tl1–xGa1–xSnxSe2 single crystals (x = 0.05; 0.1) growth together with complex studies of their optical, electric and photoelectric properties are presented. Semiconductor crystalline alloys Tl2Sе, Ga(In)2Sе3, SnSе2 possessing congruent melting features has been served as components for the quasi-ternary systems. The Tl2Se–Ga2Se3 was melted congruently at temperature 1073 K. Two compounds existied for the Tl2Sе–In2Sе3system: TlInSe2 melting congruently at 1023 K, and Tl2Sе–In2Sе3 within congruent melting nature at 1029 K. Isothermal section of the Tl2Se–Ga2Se3–SnSe2 system at 520 K have been constructed from X-ray phase and formation of the ternary compounds Tl4SnSе4, Tl2SnSе3, TlGaSе2 was confirmed. The spectral dependences of the absorption coefficients near the fundamental absorption have been studied with respect to direct as indirect dipole allowed inter-band transitions realized in the (TlGaSe2)1-x(SnSe2)x crystals for the studied temperature range. Follwing the Urbach's energy the role of electron-phonon interaction and structural disorder was analyzed. © 2019 Elsevier GmbH